Acquisition and maintenance of pluripotency are influenced by fibroblast growth factor, leukemia inhibitory factor, and 2i in bovine-induced pluripotent stem cells - Botigelli, Ramon Cesar; Pieri, Naira Carolina Godoy; Bessi, Brendon William; Machado, Lucas Simões; Bridi, Alessandra; de Souza, Aline Fernanda; Recchia, Kaiana; Neto, Paulo Fantinato; Ross, Pablo Juan; Bressan, Fabiana Fernandes; Nogueira, Marcelo Fábio Gouveia (Frontiers in Cell and Developmental Biology, 2022)
Several opportunities for embryo development, stem cells, cell fate and cell differentiation have emerged using induced stem cells (iPSCs). However, the difficulty to compare bovine iPSCs with ESCs is still persistent. Here, we present a comparison of biPSCs and bESCs. biPSCs were generated using the mouse OSKM transcription factors and derived using either bFGF or LIF in combination/or not with 2i. Additionally, bESC were used to compare the pluripotent state with these biPSCs. All cell lines were tested to evaluate the pluripotent state and used for in vitro differentiation. One biPSC and bESCs lines were injected into early embryos to assess the potential to contribute to chimeric blastocysts. The generation of biPSCs was possible in all groups. However, LIF2i treatment did not promote continuous self-renewal. All biPSCs lines demonstrated a pluripotency state and were capable of differentiation into three embryonic layers (ectoderm, endoderm, and mesoderm). Also, biPSCs and bESCs were able to contribute to chimeric blastocysts. Bovine iPSCs were generated by mOSKM transduction and cultured in our treatments. bFGF was more efficient in promoting the acquisition and maintenance of pluripotency. Additionally, biPSCs were efficient to contribute to chimeric blastocysts.